Use of autonomous recording units increased detection of a secretive marsh bird. Issue 4 (25th November 2018) - Bobay, Lucas R.; Taillie, Paul J.; Moorman, Christopher E.
Abstract: Obtaining sufficient numbers of detections during point counts to make inferences concerning the presence and abundance of secretive species, such as many species of marsh birds, can be difficult. However, autonomous recording units (ARUs) can provide extended survey windows, potentially allowing for more effective detection of elusive species. We assessed the feasibility of using both ARUs and point‐count surveys to monitor Black Rails ( Laterallus jamaicensis ) and Least Bitterns ( Ixobrychus exilis ), two secretive marsh birds of conservation concern. We identified vocalizations in ARU recordings using acoustic analysis software, and combined these observations with those from point counts to model occupancy of both species in coastal marshes of eastern North Carolina in 2016 and 2017 while accounting for variation in detection. Use of ARUs doubled the number of points where we detected Black Rails; thus, the combined point count‐ARU model yielded a greater occupancy probability for this species. However, the ARUs recorded few Least Bittern vocalizations, suggesting that successful application of ARUs may depend on the vocal complexity of focal species. Although the appropriateness of integrating ARUs with in‐person monitoring varies among species, our results illustrate that this integration increased detections of an elusive species of conservation concern.